On the Survival of Overwintering Bovine Gastrointestinal Nematode Larvae During the Subsequent Grazing Season - Smith, H. J. (1969)
Large numbers of overwintering Nematodirus helvetianus were shown to survive on Maritime marshland pastures throughout the ensuing grazing season, while the numbers of Ostertagia ostertagi and Cooperia oncophora declined rapidly after the first few weeks. It was concluded that pastures carrying heavy overwintering residual infections, particularly of N. helvetianus, may be unsafe for susceptible cattle at any time during the following grazing season.